Improvement of Electronic Structure Calculations for the Interpretation of the Emission Spectrum for Ndiii Complexes - Aravena-Ponce, D; Aravena-Ponce, D (Royal Society of Chemistry, 2025)
A protocol to correct ab initio calculated luminescence spectra of NdIII complexes is proposed. The emission spectrum of [NdIII(bipy)(tta)3] was measured to calibrate the optimal correction for the Racah parameters on top of a CASSCF calculation to attain the best energetic placement of the 4F3/2 → 4I13/2−9/2 emission lines. As interelectronic repulsion is the most important source of error in this calculation, this straightforward correction results in an accurate placement of transitions, allowing the assignment of a complex spectral shape in terms of its underlying transitions. Finally, the correction derived for [NdIII(bipy)(tta)3] was directly applied to a different NdIII complex, demonstrating the broad use of this approach. © 2025 The Royal Society of Chemistry.